1997
DOI: 10.1097/00003246-199707000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Increased artificial deadspace ventilation is a safe and reliable method for deliberate hypercapnia

Abstract: A gradual increase in artificial deadspace ventilation produces a state of deliberate hypercapnia. In our animal model, a moderate increase in artificial deadspace significantly increased the pulmonary vascular resistance but was not associated with detrimental respiratory acidemia. Larger volumes of added artificial deadspace had no detrimental effect on cardiac output, oxygen content, oxygen consumption, and systemic vascular resistance, but were associated with significant respiratory acidemia and therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In contrast, in an earlier study of convalescent prematurely born babies, a greater increase in ventilation, as assessed by respiratory inductance plethysmography (which assesses chest and abdominal wall movement) but not pneumotachography (which assesses airflow), was demonstrated in the prone compared with the supine position in response to carbon dioxide rebreathing 10. A possible explanation for the differences in the results of the two studies8 10 is the lower level of hypercapnic challenge during tube breathing 9. We, therefore, have compared the ventilatory response of convalescent prematurely born infants to a range of inspired CO 2 levels (hypercapnic challenge) in both the prone and supine positions.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…In contrast, in an earlier study of convalescent prematurely born babies, a greater increase in ventilation, as assessed by respiratory inductance plethysmography (which assesses chest and abdominal wall movement) but not pneumotachography (which assesses airflow), was demonstrated in the prone compared with the supine position in response to carbon dioxide rebreathing 10. A possible explanation for the differences in the results of the two studies8 10 is the lower level of hypercapnic challenge during tube breathing 9. We, therefore, have compared the ventilatory response of convalescent prematurely born infants to a range of inspired CO 2 levels (hypercapnic challenge) in both the prone and supine positions.…”
Section: Introductionmentioning
confidence: 75%
“…A possible mechanism for the increased risk of SIDS for prematurely born infants sleeping prone could be an impaired ability to respond to respiratory compromise, for example a raised CO 2 . Indeed, an impaired response to added dead space (tube breathing) in the prone compared with the supine position in convalescent prematurely born infants has been demonstrated8; the major stimulus during tube breathing is hypercapnia 9. In contrast, in an earlier study of convalescent prematurely born babies, a greater increase in ventilation, as assessed by respiratory inductance plethysmography (which assesses chest and abdominal wall movement) but not pneumotachography (which assesses airflow), was demonstrated in the prone compared with the supine position in response to carbon dioxide rebreathing 10.…”
Section: Introductionmentioning
confidence: 99%
“…In two healthy subjects, hypercapnia challenge (by breathing through a plastic tube with 600 mL of volume, thereby increasing the dead‐space) (25) was induced and TRUST MRI was performed before, during, and after the challenge. End‐tidal CO 2 (EtCO2) was monitored throughout the experiment and was compared with MRI results.…”
Section: Methodsmentioning
confidence: 99%
“…The major stimulus during tube breathing is hypercapnia 7. We have also demonstrated that prematurely born infants studied at a median postmenstrual age (PMA) of 36 weeks had a reduced ventilatory response to a carbon dioxide (CO 2 ) challenge in the prone compared to the supine position 8.…”
Section: Introductionmentioning
confidence: 98%